2023
DOI: 10.1101/2023.02.06.527293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TFEB-vacuolar ATPase signaling regulates lysosomal function and microglial activation in tauopathy

Abstract: Transcription factor EB (TFEB) mediates gene expression through binding to the Coordinated Lysosome Expression And Regulation (CLEAR) sequence. TFEB targets include subunits of the vacuolar ATPase (v-ATPase) essential for lysosome acidification. Single nucleus RNA-sequencing (snRNA-seq) of wild-type and PS19 (Tau) transgenic mice identified three unique microglia subclusters in Tau mice that were associated with heightened lysosome and immune pathway genes. To explore the lysosome-immune relationship, we speci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…TREM2-dependent mTOR signaling is crucial to sustain biosynthetic and energy metabolism in microglia 78 and consistent with this, we observed a dysregulation of genes involved in glycolysis and a selective upregulation of genes involved in mitochondrial oxidative phosphorylation in MAPT IVS10+16 iMGLs. Maintenance of lysosomal homeostasis is crucial to controlling microglial mTOR levels and initiating immune responses to tau pathology in the tau-P301S tauopathy mouse model 108 . Microglia activation also induces mitochondrial alterations and initiates a metabolic shift from oxidative phosphorylation to glycolysis 109 .…”
Section: Discussionmentioning
confidence: 99%
“…TREM2-dependent mTOR signaling is crucial to sustain biosynthetic and energy metabolism in microglia 78 and consistent with this, we observed a dysregulation of genes involved in glycolysis and a selective upregulation of genes involved in mitochondrial oxidative phosphorylation in MAPT IVS10+16 iMGLs. Maintenance of lysosomal homeostasis is crucial to controlling microglial mTOR levels and initiating immune responses to tau pathology in the tau-P301S tauopathy mouse model 108 . Microglia activation also induces mitochondrial alterations and initiates a metabolic shift from oxidative phosphorylation to glycolysis 109 .…”
Section: Discussionmentioning
confidence: 99%
“…Studying cell vulnerability in AD is important to understand disease progression, reveal biomarkers, and identify therapeutic targets. snRNA-seq serves as an ideal method to study cell vulnerability and several recent studies have employed snRNA-seq in different AD models and human patients (Lau et al, 2020;Mathys et al, 2023;Sziraki et al, 2023;Wang et al, 2024;Wu et al, 2023). Out of necessity, most of these studies have focused on a specific brain region and identified specific cell types that are selectively vulnerable.…”
Section: Cell Type Vulnerability In Admentioning
confidence: 99%
“…For example, in the human prefrontal cortex, it was found that the most vulnerable cell types in AD tissues are three subtypes of SST+ inhibitory neurons (Mathys et al, 2023). In a PS19 AD mouse model, we found that granule cells in the hippocampus show the highest vulnerability among different types of neurons (Wang et al, 2024). Here, we took a novel approach and focused on comprehensively comparing peripheral sensory neurons with CNS neurons in AD models.…”
Section: Cell Type Vulnerability In Admentioning
confidence: 99%
“…In the context of AD, recent studies indicate that metabolic defects in microglia contribute to AD [76][77][78][79][80][81][82][83][84]. Microglia's survival and function depend on adequate energy supply.…”
Section: C3ar In Ad: Hif-1 and Immunometabolic Regulationmentioning
confidence: 99%